2016
DOI: 10.1111/aogs.12877
|View full text |Cite
|
Sign up to set email alerts
|

Can adverse maternal and perinatal outcomes be predicted when blood pressure becomes elevated? Secondary analyses from the CHIPS (Control of Hypertension In Pregnancy Study) randomized controlled trial

Abstract: IntroductionFor women with chronic or gestational hypertension in CHIPS (Control of Hypertension In Pregnancy Study, NCT01192412), we aimed to examine whether clinical predictors collected at randomization could predict adverse outcomes.Material and methodsThis was a planned, secondary analysis of data from the 987 women in the CHIPS Trial. Logistic regression was used to examine the impact of 19 candidate predictors on the probability of adverse perinatal (pregnancy loss or high level neonatal care for >48 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…The current study also suggested that association magnitudes between SBP trajectories and the above-mentioned neonate outcomes depended mainly on the absolute SBP values in the third trimester. Consistently, studies found that BP elevation from the second trimester to the third trimester was associated with an increased risk of adverse birth outcomes [ 10 , 45 ]. What’s more, a Chinese study found a dose-response relationship between maternal BP and adverse birth outcomes, and BP in the third trimester showed the strongest associations [ 46 ].…”
Section: Discussionmentioning
confidence: 74%
“…The current study also suggested that association magnitudes between SBP trajectories and the above-mentioned neonate outcomes depended mainly on the absolute SBP values in the third trimester. Consistently, studies found that BP elevation from the second trimester to the third trimester was associated with an increased risk of adverse birth outcomes [ 10 , 45 ]. What’s more, a Chinese study found a dose-response relationship between maternal BP and adverse birth outcomes, and BP in the third trimester showed the strongest associations [ 46 ].…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, the administration of prophylactic calcium and or aspirin may have caused treatment paradox [84] that modified the effect of the risk factors on the development and outcomes of PE among the participants. The possible alteration of the circulating levels of angiogenic factors by aspirin reported in a previous study [85] is noted.…”
Section: Discussionmentioning
confidence: 99%
“…In the CHIPS trial, women randomized to less tight control more frequently developed severe hypertension, and predictive modeling was unable to identify which women were destined to do so. 2 , 3 Both severe hypertension and preeclampsia, a recognized risk marker for adverse outcome, were common (33.9% and 47.3%, respectively) and often developed in the same woman (25.3%), but neither severe hypertension nor preeclampsia fully accounted for all women with one or more of the adverse outcomes considered. However, severe hypertension was associated with higher rates of each of the CHIPS primary perinatal outcome, birth weight <10th percentile, preeclampsia, delivery at <34 or 37 weeks, platelets <100×10 9 /L, elevated liver enzymes with symptoms, and maternal length of hospital stay ≥10 days.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, predictive modeling did not demonstrate that women destined to develop subsequent severe hypertension could be identified by clinical characteristics at randomization, when a BP management strategy was instituted. 3 …”
mentioning
confidence: 99%
See 1 more Smart Citation